Enkapsulasi Beberapa Jenis Trichoderma. sp. pada Benih Kedelai untuk Mengendalikan Penyakit Sclerotium rolfsii Sacc. - Eli Saputri; Lisnawita Lisnawita; Mukhtar Iskandar Pinem (Universitas Sumatera Utara, 2015)
Encapsulation of Some Trichoderma sp. on Soybean Seed to Control Sclerotium rolfsii Sacc. The research aimed was to get species of Trichoderma which mixed alginat or tapioca encapsulated soybean seed to inhibiting S. rolfsii. This research was conducted in Laboratory of Plant Disease, Faculty of Agriculture, University of Sumatera Utara, use Randomized Block Design 3 factors and sixteen treatments : alginate, tapioca, alginate + S. rolfsii, tapioca + S. rolfsii, alginate + T. harzianum, tapioca + T. harzianum, alginate + T. koningii, tapioca + T. koningii, alginate + T. viridae, tapioca + T. viridae, alginate + T. harzianum + S. rolfsii, tapioca + T. harzianum + S. rolfsii, alginate + T. koningii + S. rolfsii, tapioca + T. koningii + S. rolfsii, alginate + T. viridae + S . rolfsii, tapioca + T. viridae + S. rolfsi, respectively with four replications. The result showed that all of Trichoderma sp. isolates which mixed alginat or tapioca have high viability in inhibiting S. rolfsii. All of Trichoderma isolates enabled to reduce damping off on soybean seed. The treatments alginate + T. harzianum + S. rolfsii, tapioca + T. harzianum + S. rolfsii, alginate + T. koningii + S. rolfsii have high viability in inhibiting damping off by 100 % and followed tapioca + T. viridae + S. rolfsi and alginate + T. viridae + S . rolfsii (75%) and tapioca + T. koningii + S. rolfsii (50%).Key words: encapsulated, damping off, Sclerotium rolfsii, Trichoderma sp.